Synthesis and Antitumor Evaluation of Menthone-Derived Pyrimidine-Urea Compounds as Potential PI3K/Akt/mTOR Signaling Pathway Inhibitor - Huang, Mei; Duan, Wengui; Chen, Naiyuan; Lin, Guishan; Wang, Xiu (Frontiers in Chemistry, 2022)
A series of novel menthone derivatives bearing pyrimidine and urea moieties were designed and synthesized to explore more potent natural product-derived antitumor agents. The structures of the target compounds were confirmed by FTIR, NMR, and HRMS. The in vitro antitumor activity of the target compounds was evaluated by standard MTT(methyl thiazolytetrazolium) assay against four human cancer cell lines of A549, Hela, MCF-7 and MGC-803, and compared with the commercial antitumor drug fluorouracil(5-FU). The bioassay results revealed that most of the target compounds exhibited better antiproliferative activity than that of the positive control 5-FU, in which compounds 4i, 4g, 4s, and 4m had the best IC50 values of 6.04 ± 0.62 µM, 3.21 ± 0.67 µM, 19.09 ± 0.49 µM, and 18.68 ± 1.53 µM, respectively, against Hela, MGC-803, MCF-7, and A549. As a representative compound, compound 4i was employed to investigate the cell cycle and cell apoptosis in Hela Cells by Annexin-V/PI dual staining, and the results showed that compound 4i could induce cell apoptosis in Hela cells in a dose-dependent manner and arrest the cell cycle in G2 phase. Furthermore, the proteins and pathways which involved in the antitumor (Hela) activity of 4i were predicted and confirmed with the network pharmacology and Western blot experiments. The binding modes and the binding sites interactions between the active compound 4i and the target proteins were predicted preliminarily by the molecular docking method.